Optimization of Outcomes in Post-Traumatic Facial Reconstruction Surgery: Comparative Analysis of Graft Techniques and Biocompatible Prosthetic Materials - Arcondo, Jorge Luis Borda; Mello, Arnaldo Almendros (Journal of Posthumanism, 2025)
Reconstructing the human aspect in post-traumatic facial reconstruction is one of the most difficult jobs in plastic and maxillofacial surgery. It offers a wide spectrum of approaches in the attempt to restore facial functionality and aesthetics. This article focuses on the difference in outcomes between autologous grafts and biocompatible prosthetic materials in facial reconstructive surgeries. A review of recently published clinical case reports and randomised controlled trials from 2018 to 2023 was conducted. It turned out that long-term autografts produced superior functional and aesthetic results, and prosthetic materials allowed for faster recovery with fewer initial surgical complications. The clinical implications of such findings are discussed.